The effect of temperature and H2SO4 concentration and soaking time on breaking dormancy of sengon seed (Falcataria moluccana (Miq.) Barneby & J.W. Grimes) - Olivia Anafarida; Ika Oksi Susilawati; Rusmana Rusmana (Jurnal GALAM, 2021)
Sengon (Falcataria moluccana (Miq.) Barneby & J.W. Grimes) is a Leguminoceae plant that is useful as material for making panel wood, furniture wood and trees that can rehabilitate critical land. Sengon seeds experience a period of dormancy and need to be managed. The purpose of this study is to determine the effect of temperature 600C and 50% H2SO4 concentration and soaking time on sengon seed germination. A complete randomized design (CRD) with two factors were used as research design. The first factor was the air temperature treatment of kontrol (A1), 60o C (A2), 50% H2SO4 (A3) and which consisted of 3 levels of treatment. The second factor was soaking time (T); T1: 35 minutes, T2: 8 hours. The results showed that the best combination of treatment and immersion time for all germination parameters of sengon seed is soaking seed at 60o C water for 8 hours Key words: Temperature water, H2SO4, Paraserianthes falcataria, germination